2011
DOI: 10.1095/biolreprod.110.085753
|View full text |Cite
|
Sign up to set email alerts
|

Select Nutrients in the Ovine Uterine Lumen. VIII. Arginine Stimulates Proliferation of Ovine Trophectoderm Cells Through MTOR-RPS6K-RPS6 Signaling Cascade and Synthesis of Nitric Oxide and Polyamines1

Abstract: During the peri-implantation period in sheep, L-arginine (L-Arg) in the uterine lumen is an essential substrate for the synthesis of nitric oxide (NO), by nitric oxide synthase (NOS), and polyamines, via arginase and ornithine decarboxylase, that are required for survival and development of ovine conceptuses (embryo and its extraembryonic membranes). L-Arginine can stimulate hypertrophy, hyperplasia, and differentiation of the ovine conceptus trophectoderm; however, the responsible signal transduction cascade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 77 publications
1
62
0
Order By: Relevance
“…Amino acids are critical to pregnancy because of its influence on embryo and fetal growth and development (Kim et al 2011, Wu 2010. Our previous study demonstrated that dietary arginine supplementation during early pregnancy enhanced the number of embryos implanted and the expression of iNOS and eNOS in implantation sites was increased in rats fed the arginine-supplemented diet (Zeng et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Amino acids are critical to pregnancy because of its influence on embryo and fetal growth and development (Kim et al 2011, Wu 2010. Our previous study demonstrated that dietary arginine supplementation during early pregnancy enhanced the number of embryos implanted and the expression of iNOS and eNOS in implantation sites was increased in rats fed the arginine-supplemented diet (Zeng et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Intrauterine injection of DFMO on d4 of pregnancy inhibited embryonic development and embryogenesis in rats (Méndeza et al 1983). Previous study demonstrated that arginine stimulated proliferation of ovine trophectoderm cells via mTOR signaling pathway and nitric oxide and polyamines (Kim et al 2011). We hypothesize that dietary arginine supplementation during early pregnancy may activate PI3K-PKB-mTOR signaling pathway, which could increase the expression of uterine iNOS and eNOS and inhibition of polyamine synthesis could increase NO production and release.…”
Section: Introductionmentioning
confidence: 85%
“…Cells grown in serum-free specialized medium and specialized medium containing 10% FBS served as negative and positive controls, respectively. Cell numbers were determined as described previously (44)(45)(46)(47)(48).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of glucose and fructose on phosphorylation of RPS6K, EIF4EBP1, and RPS6 were determined by immunofluorescence microscopy as previously described (44,45). Cells probed with rabbit anti-human polyclonal p-RPS6K IgG (Thr421/Ser424) at a 1:200 di- Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, signaling pathways mediated by Arg to effect proliferation of ovine trophectoderm (oTr) cells were assessed using NO donors (SNAP and DETA) and putrescine (a precursor for spermidine and spermine; Kim et al, 2011). L-NAME (an inhibitor of NOS) and Nor-NOHA (an inhibitor of arginase) were also used to assess pathways activated via Arg.…”
Section: Argininementioning
confidence: 99%